Numerical Simulation and Test of the Disturbance Air Suction Garlic Seed Metering Device - Chunling Zhang; Xinyi Zhang; Zihao Zheng; Xiaodong Xie; Lichao Liu; Liqing Chen (Machines, 2022)
In order to solve the problems of high missed rate and easily damaged seeds in traditional garlic metering devices, an air suction garlic seed metering device was designed. The critical components include a seed tray and a seed disturbing tooth. Seed contour curve fitting and a discrete element method were used to determine the initial parameters. The optimal parameter combinations were obtained through fluid dynamics simulation. With a higher pass seeding rate and a lower missed seeding rate as the goal, the device has been optimized for parameters. The best combination of parameters was obtained: the number of type holes was 9; the diameter of holes was 7.2 mm; the forward speed was 1 km/h; the working negative pressure was −5.5 kPa; the pass seeding rate was 88.54%; and the missed seeding rate was 6.34%. Field trials had shown that the air suction garlic seed metering device designed in this study satisfied the requirements of garlic cultivation. Three tests were conducted and a pass rate of 87.83% and a missed rate of 6.85% were obtained.